Peningkatan Kinerja Rotor Savonius Dengan Mengembangkan Sudu Baru Berbasis Airfoil - Rendi Rendi; Budi Hartadi; Muhammad Firman; Muhammad Irfansyah (Jurnal Engine: Energi, Manufaktur, dan Material, 2022)
The development of new and renewable energy is currently a top priority for the international community, as energy needs continue to increase while fossil fuels are running low. The Savonius rotor turbine is one of the most widely used turbines but has low efficiency. This study aims to improve the performance of the Savonius turbine by developing a new blade based on airfoil which is simulated in CFD. There are 2 blade models to be simulated, namely the RD-1 model and the RD-2 model, then the simulation results are compared with the conventional blade. The results of the study can be said that the new airfoil-based blade can improve the performance of the Savonius turbine, the increase occurs in the TSR value which is better than the conventional blade. The highest Cp is 0.148 on the RD-2 model blade with a maximum TSR of 0.8